2013
DOI: 10.1371/journal.pone.0078708
|View full text |Cite
|
Sign up to set email alerts
|

Amplitude of Low Frequency Fluctuation Abnormalities in Adolescents with Online Gaming Addiction

Abstract: The majority of previous neuroimaging studies have demonstrated both structural and task-related functional abnormalities in adolescents with online gaming addiction (OGA). However, few functional magnetic resonance imaging (fMRI) studies focused on the regional intensity of spontaneous fluctuations in blood oxygen level-dependent (BOLD) during the resting state and fewer studies investigated the relationship between the abnormal resting-state properties and the impaired cognitive control ability. In the prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
58
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 68 publications
(67 citation statements)
references
References 31 publications
7
58
0
2
Order By: Relevance
“…It has drawn scientific attention from academia around the world (Christakis, 2010;Durkee et al, 2012). Numerous studies had detected the possible neural mechanisms of the IGD and suggested that it may be related to the impaired cognitive control (Dong et al, 2011a(Dong et al, , 2011b(Dong et al, , 2013Yuan et al, 2013aYuan et al, , 2013b. More and more findings suggested that cognitive control ability is not only associated with the isolated operations of single brain areas but also is related with the connections within brain core neurocognitive networks (Bressler and Menon, 2010;Menon and Uddin, 2010;Menon, 2011;Uddin et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…It has drawn scientific attention from academia around the world (Christakis, 2010;Durkee et al, 2012). Numerous studies had detected the possible neural mechanisms of the IGD and suggested that it may be related to the impaired cognitive control (Dong et al, 2011a(Dong et al, , 2011b(Dong et al, , 2013Yuan et al, 2013aYuan et al, , 2013b. More and more findings suggested that cognitive control ability is not only associated with the isolated operations of single brain areas but also is related with the connections within brain core neurocognitive networks (Bressler and Menon, 2010;Menon and Uddin, 2010;Menon, 2011;Uddin et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Although the accurate contribution of these brain networks to cognitive control remains controversial, one theory is that the salience network (SN) -which includes the ACC and insula -regulates dynamic changes in other networks to modulate cognitive function (Bonnelle et al, 2012;Uddin et al, 2011). Previous studies had connected the regional brain abnormalities and impaired cognitive control in IGD, such as the correlation between the abnormal OFC and response errors during incongruent condition measured by Stroop task (Yuan et al, 2013a(Yuan et al, , 2013b. Values are expressed as mean7standard deviation (SD).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations